2022
DOI: 10.3389/fpls.2022.922963
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genetic factors regulating chlorophyll and carotenoid biosynthesis in red pepper fruit

Abstract: Chlorophylls and carotenoids are synthesized in the chloroplast and chromoplast, respectively. Even though the two pigments are generated from the same precursor, the genetic correlation between chlorophyll and carotenoid biosynthesis has not yet been fully understood. We investigated the genetic correlation of chlorophyll and carotenoid biosynthesis during fruit ripening. Two recombinant inbred lines populations, "Long Sweet" × "AC2212" ("LA") RILs derived from a cross between Capsicum annuum "Long Sweet" wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Indeed, DXS expression levels were significantly reduced in all genotypes compared to other tested genes, suggesting a significant reduction in pigment synthesis in older tissues (Figure 6). Similar DXS reduction during developmental stages was observed in red pepper fruits [56].…”
Section: Relationship Between Biosynthetic Gene Expression and Carote...supporting
confidence: 80%
“…Indeed, DXS expression levels were significantly reduced in all genotypes compared to other tested genes, suggesting a significant reduction in pigment synthesis in older tissues (Figure 6). Similar DXS reduction during developmental stages was observed in red pepper fruits [56].…”
Section: Relationship Between Biosynthetic Gene Expression and Carote...supporting
confidence: 80%
“…On the contrary, the ripening process of pepper fruits involves many changes at the phenotypic, transcriptomic, proteomic, and metabolomic levels, and its big genome size, in comparison to other Solanaceae, makes its analysis complex (Dyachenko et al 2020 ; Razo-Mendivil et al 2021 ; Esposito et al 2022 ; Kovács et al 2022 ; Del Giúdice et al 2023 ). Recently, “omic” approaches have been carried out to study specific aspects of the ripening process (Chiaiese et al 2019 ; Dubey et al 2019 ; Zuo et al 2019 ; Lopez-Ortiz et al 2021 ; Rödiger et al 2021 ; Momo et al 2022 ; Villa-Rivera et al 2022 ; Song et al 2022 ; Liu et al 2023 ; Wang et al 2024 ) which are dependent on the variety, environmental growth conditions, fruit position, and ripening stage (Ribes-Moya et al 2020 ; Jang et al 2022 ; Lahbib et al 2023 ; Guijarro-Real et al 2023 ; Islam et al 2023 ). Despite the increase in information on the ripening of pepper fruits, to our knowledge, there is no data on the LAP in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative evaluation of pigments revealed that Xylanase was the only BS solution that significantly impacted on chlorophyll and carotenoid content resulting in altered Chl a:b and Chls:Car ratios. The decrease in Chl b may be due to its conversion into Chl a, via the so-called "chlorophyll cycle" [40] to optimize adaptation of plants to varying light conditions [41][42][43][44]. The chlorophyll a:b ratio is a highly stable value that is generally used as a parameter to monitor plant oxidative stress status/tolerance because it is decreased by oxidative damage, according to its severity [45].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, given the stable levels of Chl a alongside an increase in Car, it is more plausible that Chl b is either degraded or transformed into carotenoids. This assumption is based on the shared precursor of both chlorophylls and carotenoids, namely GGPP (geranyl geranyl pyrophosphate) [43]. The rise in carotenoid content has been commonly reported in plants treated with several types of BSs [47,48].…”
Section: Discussionmentioning
confidence: 99%